2014
DOI: 10.3168/jds.2014-8066
|View full text |Cite
|
Sign up to set email alerts
|

Novel extraction method of genomic DNA suitable for long-fragment amplification from small amounts of milk

Abstract: Isolation of genomic DNA is a prerequisite for assessment of milk quality. As a source of genomic DNA, milk somatic cells from milking ruminants are practical, animal friendly, and cost-effective sources. Extracting DNA from milk can avoid the stress response caused by blood and tissue sampling of cows. In this study, we optimized a novel DNA extraction method for amplifying long (>1,000 bp) DNA fragments and used it to evaluate the isolation of DNA from small amounts of milk. The techniques used for the separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 16 publications
2
23
1
Order By: Relevance
“…Theoretically, pure DNA solutions have an A 260 /A 280 of above 1.8, but we found that the ratio of absorbance (A 260 /A 280 ) of all DNA solutions was below 1.8, probably due to contamination by phenols or proteins. For the raw milk, the resulting ratio (1.60) was lower than that (1.79) reported by Pokorska et al (2016), but similar to that (1.65) reported by Liu et al (2014). These differences in purity of the raw milk samples might be attributed to the different extraction method we used.…”
Section: Effect Of Heat Treatment On Dna Quality Parameterssupporting
confidence: 48%
See 2 more Smart Citations
“…Theoretically, pure DNA solutions have an A 260 /A 280 of above 1.8, but we found that the ratio of absorbance (A 260 /A 280 ) of all DNA solutions was below 1.8, probably due to contamination by phenols or proteins. For the raw milk, the resulting ratio (1.60) was lower than that (1.79) reported by Pokorska et al (2016), but similar to that (1.65) reported by Liu et al (2014). These differences in purity of the raw milk samples might be attributed to the different extraction method we used.…”
Section: Effect Of Heat Treatment On Dna Quality Parameterssupporting
confidence: 48%
“…(), but similar to that (1.65) reported by Liu et al . (). These differences in purity of the raw milk samples might be attributed to the different extraction method we used.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The DNA was extracted from 10-mL milk according to the method described in our previous work (Liu et al, 2014). The method of DNA extraction could avoid a stress response in the sampled animals affecting milk production compared with traditional extraction methods, which obtained DNA from blood and organ tissues (Buitkamp & Gotz, 2004).…”
Section: Dna Extractionmentioning
confidence: 99%
“…Compared to biochemical analysis, traditional sensory, chemical and instrumental methods used to assess milk quality are limited in analyzing large-scale samples (Guy & Fenaille, 2006;Korel & Balaban, 2002;Larsen, Kidmose, Kristensen, Beaumont, & Mortensen, 2013;Mariaca & Bosset, 1997;Marsili, 2000). In recent years, molecular techniques have been one of the powerful tools in quality inspection of dairy products and in research of molecular nutrition (Liu, Gao, Yang, Ku, & Zan, 2014). Whether this method can be utilized to monitor the milk quality remains unknown.…”
Section: Introductionmentioning
confidence: 99%